2008
DOI: 10.2193/2007-165
|View full text |Cite
|
Sign up to set email alerts
|

Waterbird Response to Wetlands Restored Through the Conservation Reserve Enhancement Program

Abstract: Conservation programs that facilitate restoration of natural areas on private land are one of the best strategies for recovery of valuable wetland acreage in critical ecoregions of the United States. Wetlands enrolled in the Conservation Reserve Enhancement Program (CREP) provide many ecological functions but may be particularly important as habitat for migrant and resident waterbirds; however, use of, and factors associated with use of, CREP wetlands as stopover and breeding sites have not been evaluated. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…The Des Moines Lobe hosts 72 of these CREP sites in 29 counties. The resulting wetlands appear to provide additional ecosystem services such as habitat for migrating waterfowl (O'Neal et al, 2008), however, for many organisms, such as amphibians the related costs of living within a matrix of highly modified habitat have not been determined. For example, the value of increased habitat for species with low vagility (e.g., amphibians) is assumed to be high, but benefits may be negated if the quality of the habitat is insufficient to support amphibian populations' overtime.…”
Section: Introductionmentioning
confidence: 99%
“…The Des Moines Lobe hosts 72 of these CREP sites in 29 counties. The resulting wetlands appear to provide additional ecosystem services such as habitat for migrating waterfowl (O'Neal et al, 2008), however, for many organisms, such as amphibians the related costs of living within a matrix of highly modified habitat have not been determined. For example, the value of increased habitat for species with low vagility (e.g., amphibians) is assumed to be high, but benefits may be negated if the quality of the habitat is insufficient to support amphibian populations' overtime.…”
Section: Introductionmentioning
confidence: 99%
“…Not sur prisingly, the intensity of moist soil management had an important effect on wintering waterfowl response, as others have found for birds during spring and summer (Kaminski et al 2006, O'Neal et al 2008. WRP sites with the greatest increases in site soil wetness after resto ration had the greatest post-restoration waterfowl use.…”
Section: Resultsmentioning
confidence: 60%
“…The primary objective of the RFL project was to regulate floods, and it focused on hydrological restoration measures such as removing dikes that also increased the area of wetlands and improved the habitat quality for migratory birds. O'Neal et al (2008) also found that successful hydrological restoration measures improved habitat quality and increased waterfowl populations. However, our study also shows that despite of restoration activities, change of many other human activities, such as discontinuing of cultivation, also has great contribution in improving the habitat.…”
Section: Conclusion and Discussionmentioning
confidence: 87%
“…Our research work also showed that even though the restoration work was not targeted at waterfowl and had not been implemented for a long time, the restoration engineering (and especially the RFL project) can improve habitats in the study sites. The management of wetland habitats to restore favorable characteristics can benefit habitats of diverse waterfowl species (Erwin and Beck 2007;O'Neal et al 2008;Ma et al 2010). Fang et al (2006) also showed that the RFL project improved biodiversity in the Poyang Lake wetland, and that the populations of some overwintering migratory birds increased.…”
Section: Conclusion and Discussionmentioning
confidence: 99%